Adaptive diversity and drought tolerance in Castanea sativa assessed through EST-SSR genic markers. (26th February 2019) - Alcaide, Francisco; Solla, Alejandro; Mattioni, Claudia; Castellana, Simone; Martín, M Ángela
Abstract: Increasing drought conditions in Mediterranean countries are negatively impacting the survival and productivity of Castanea sativa Mill. The study aimed to select EST-SSR markers associated with drought stress developed in Quercus spp. and evaluate their transferability and polymorphism in C. sativa . Eight EST-SSR markers were selected to examine the adaptive potential of four wild populations of C. sativa in relation to drought tolerance. To validate markers, offspring of the study trees were water stressed and their drought tolerance was assessed. EST-SSR markers and leaf wilting of seedlings after drought treatment revealed a north–south gradient of C. sativa populations. The heritability value obtained for the 'leaf wilting' trait ( h 2 = 0.26 ± 0.08) indicated that selection for drought tolerance is possible. The differentiation coefficient of markers showing neutral selection ( F ST = 0.080) was lower than the quantitative genetic differentiation of populations ( Q ST = 0.28), indicating that selection of drought tolerant trees acted spatially in a heterogeneous manner. When assessing the genetic structure of populations, FIR080 was identified as outlier locus under positive selection. When assessing the phenotypic tolerance to drought of offspring, GOT004 and GOT045 were identified as outlier loci under balancing selection and FIR059 was identified as an outlier locus under positive selection. FIR059 showed three private alleles for drought-susceptible individuals and two private alleles for drought-tolerant individuals and could therefore be considered as a candidate marker to predict drought tolerance in unstressed C. sativa trees. Combined use of functional markers and phenotypic traits is a powerful approach to determine genetic variation at the adaptive level in C. sativa . The results illustrate the potential of EST-SSR markers for early selection of drought tolerant plant material.